Highlights of practical applications of scalable multi-agent systems : the PAAMS collection : International Workshops of PAAMS 2016, Sevilla, Spain, June 1-3, 2016. Proceedings /: the PAAMS collection : International Workshops of PAAMS 2016, Sevilla, Spain, June 1-3, 2016. Proceedings. (2016) - Unknown
No abstract available